Recent technologies for detection of milk contaminants: characterization and mechanism of action: a review article - Osama M. Darwesh; Amr Mostafa; Hoda S. El-Sayed; Ibrahim A. Matter (Discover Food)
Abstract The dairy industry represents a large part of the global economy. Despite its importance to humans, especially children and infants, it is subject to profit and loss policies, which may (unfortunately) lead some to use fraudulent methods in raw materials or additives. Adulteration may occur by adding some ingredients that hide damage or deficiency in one of its components or using spoiled or contaminated raw materials. Therefore, many traditional methods have long been developed and applied to quantitatively and qualitatively evaluate the quality of milk and dairy products. In addition, tremendous analytical techniques based on modern biotechnology and nanotechnology to quickly detect and quantify basic milk contaminants were developed. Therefore, this review discusses chemical, physical, and biological contaminants as well as the prevailing adulteration methods of milk and dairy products. Moreover, detection approaches for milk contaminants have been reported, including traditional techniques, modern biochemical and immunoassays, sensors, and biosensors. In addition, the role of nanotechnology in milk contaminant detection has been discussed.